2011
DOI: 10.1258/ebm.2011.011023
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent hypoxia conditioning prevents endothelial dysfunction and improves nitric oxide storage in spontaneously hypertensive rats

Abstract: Although intermittent hypoxia is often associated with hypertension, experimental and clinical studies have demonstrated definite antihypertensive effects of some intermittent hypoxia conditioning (IHC) regimens. Mechanisms of this antihypertensive response are unknown. Endothelial dysfunction related to disturbed synthesis and/or reduced availability of nitric oxide (NO) has been linked to hypertension. Thus, experiments were conducted to determine if IHC can improve endothelium-dependent relaxation and forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 37 publications
1
30
0
1
Order By: Relevance
“…Akt activation may also provide protection via increased eNOS and augmented NO stores. In fact, the anti-hypertensive effect of IH in young spontaneously hypertensive rats is associated with prevention of endothelial dysfunction and with increased accumulation of NO stores in vascular walls due to augmented eNOS activity [62]. The ability of IH to increase eNOS is shared also in OSA-like models at the level of the carotid body [63].…”
Section: Discussionmentioning
confidence: 99%
“…Akt activation may also provide protection via increased eNOS and augmented NO stores. In fact, the anti-hypertensive effect of IH in young spontaneously hypertensive rats is associated with prevention of endothelial dysfunction and with increased accumulation of NO stores in vascular walls due to augmented eNOS activity [62]. The ability of IH to increase eNOS is shared also in OSA-like models at the level of the carotid body [63].…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiments have shown that, among various types of adaptation, hypoxic conditioning is the most effective in stimulating nitric oxide synthesis and storage [9,12]. Beneficial effects on nitric oxide metabolism apparently underlie hypoxiainduced prevention of endothelial dysfunction and the antihypertensive effect of hypoxia observed in spontaneously hypertensive rats [10,[13][14][15]. Thus, the present study was designed to evaluate the effect of normobaric intermittent hypoxia conditioning (IHC) on BP and nitric oxide production in patients with stage 1 arterial hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…IH can protect the heart against ischemia-reperfusion injury (197) by improving against ischemia-induced contractile dysfunction (31, 127), endothelial dysfunction (110,111), arrhythmias (110,116,209), and cell death (45, 89). Also, IH treatment can promote higher resistance to arrhythmias during acute myocardial ischemia and prevent the development of atherosclerosis in rabbits (88).…”
Section: Whenmentioning
confidence: 99%
“…This protection has been ascribed to the higher myocardial vascularity, coronary blood flow, cardiomyoglobin, and expression of antioxidant proteins induced by IH (211). Other investigators have reported antihypertensive effects of conditioning IH exposures (9 -10% O 2 , 5-10 min, 5-8 times per day) in young spontaneous hypertensive rats, which have been associated with prevention of endothelial dysfunction and with increased accumulation of nitric oxide (NO) in vasculature (111). In addition, IH appears to provide a therapeutic effect on permanent coronary artery ligation-induced myocardial infarction by reducing the infarct size, myocardial fibrosis, and apoptosis (202).…”
Section: Whenmentioning
confidence: 99%